DEVELOPMENT OF AGRO-INDUSTRIAL COMPLEX TECHNOLOGIES AND METHODOLOGY OF SCIENTIFIC SEARCH - Panfilov V.A. (Техника и технология пищевых производств)
According to spatially - temporary organization, structure and functioning, modern technologies of Agro-Industrial Complex respond to the mathematical method of a research based on the probabilistic, statistical principle. Due to the of complication of existing technologies and creating new complex ones belonging to the whole class, a new methodological approach arises in the modern science. In the article it is offered to consider seven main milestones which will become reference points in carrying out fundamental scientific researches during creation of an industrial basis of food production by consolidation into system complexes of agricultural raw materials technologies and technologies of their conversion with the high level of automation and computerization. Each milestone is an element of the strategy of scientific search in the development of the technologies’ total combination. According to the first milestone it is necessary to determine consistent patterns of technology functioning as systems of processes. The second milestone requires judgment about the need for the analysis and synthesis process application that in its turn leads to creation of the model of an object, either determined or stochastic. The third milestone considers the main requirements to which technologies (system of processes) as objects of research and optimization should respond. The fourth milestone implies the creation of the graphical model of a system complex technology thanks to the consistent use of the analysis and synthesis. The subsequent two milestones imply diagnostics of technological system from the point of view of its quality functioning and the subsequent process of adjustment for the purpose of increasing its efficiency. The last milestone implies search for the most effective methods of energy supply to the processes of production, storage and conversion of agricultural raw materials into food. Thanks to the formulated strategy of scientific research in the development of the combination of technologies it is possible to see its methodological differences from the strategy applied in the fulfillment of traditional tasks for separate processes enhancement.